Analysis and improvement of a double-image encryption scheme using pixel scrambling technique in gyrator domains. (March 2015) - Chen, Jun-xin; Zhu, Zhi-liang; Fu, Chong; Zhang, Li-bo; Yu, Hai
Abstract: Recently, a double-image encryption scheme using local pixel scrambling technique and gyrator transform has been proposed [Opt Lasers Eng 2013; 51: 1327–31]. Through our simulations, there is serious cross-talk disturbance in the phase-based image when the encrypted data undergoes noise perturbation or occlusion attack. The disturbance will cause serious deterioration in the retrieved phase-based image and bring about visibility ambiguities to the receiver, and hence downgrades the practicability of the cryptosystem. In this paper, detailed analysis of the cross-talk disturbance in the original scheme will be firstly given out, and then the corresponding improvement is subsequently proposed. Numerical simulations results indicate that the improved scheme well address the cross-talk disturbance and further enhance the security of the original cryptosystem. Highlights: Cross-talk disturbance analysis of a double-image encryption scheme is given out. A pre-processing lightweight pixel confusion approach is proposed to improve the original encryption scheme. Simulations results prove the security enhancements of the improved scheme.